The transcription factor BACH1 at the crossroads of cancer biology: From epithelial–mesenchymal transition to ferroptosis - Igarashi, Kazuhiko; Nishizawa, Hironari; Saiki, Yuriko; Matsumoto, Mitsuyo (The Journal of biological chemistry, 2021)
The progression of cancer involves not only the gradual evolution of cells by mutations in DNA but also alterations in the gene expression induced by those mutations and input from the surrounding microenvironment. Such alterations contribute to cancer cells' abilities to reprogram metabolic pathways and undergo epithelial-to-mesenchymal transition (EMT), which facilitate the survival of cancer cells and their metastasis to other organs. Recently, BTB and CNC homology 1 (BACH1), a heme-regulated transcription factor that represses genes involved in iron and heme metabolism in normal cells, was shown to shape the metabolism and metastatic potential of cancer cells. The growing list of BACH1 target genes in cancer cells reveals that BACH1 promotes metastasis by regulating various sets of genes beyond iron metabolism. BACH1 represses the expression of genes that mediate cell–cell adhesion and oxidative phosphorylation but activates the expression of genes required for glycolysis, cell motility, and matrix protein degradation. Furthermore, BACH1 represses FOXA1 gene encoding an activator of epithelial genes and activates SNAI2 encoding a repressor of epithelial genes, forming a feedforward loop of EMT. By synthesizing these observations, we propose a “two-faced BACH1 model”, which accounts for the dynamic switching between metastasis and stress resistance along with cancer progression. We discuss here the possibility that BACH1-mediated promotion of cancer also brings increased sensitivity to iron-dependent cell death (ferroptosis) through crosstalk of BACH1 target genes, imposing programmed vulnerability upon cancer cells. We also discuss the future directions of this field, including the dynamics and plasticity of EMT.